ComCog - encapsulation - Hernández Pérez, Celia; Loureda Lamas, Óscar; Teucher, Mathis; Cruz, Adriana (Universität, 2025)
Eye Tracking Data comparing Encapsulation and Coreference across different levels of informativity of the referential expression.
Gesehen am 24.02.2025
Keywords: Forschungsdaten; Datenbank